Intelligent devices for tennis rackets - Fernández-Garcia, A. I.; Torres-Luque, G. (Coaching and Sport Science Review, 2018)
The current technological advance within the field of sport is an undeniable fact, and this includes a speciallist sport such as tennis. In line with these changes, there are different devices in the market today to help players` technical and kinetic analysis. Coaches sometimes cast doubt about these devices` performance and technical characteristics. This article intends to ntroduce the tools that are currently marketed that offer technical and kinetic information about tennis players.